Impoverishment assessment of slum dwellers after off-site and on-site resettlement :a case of Indore - Patel, Sejal (2020)
This paper is an attempt to assess the impacts of off-site and on-site resettlement projects in Indore by comparing slum dwellers lives before and after the implementation of the projects, complimenting and corroborating a sister paper based on fieldwork in Ahmedabad (Patel, Sliuzas, Mathur, & Miscione, fortcoming). The impact analysis is based on the indicators of impoverishment risks due to displacement and resettlement formulated by Cernea (2000a) in his Impoverishment Risks and Reconstruction (IRR) model. The findings indicates the presence of the following forms of impoverishment which Cernea proposed for the displacees: significant loss in household assets, increased joblessness or unemployment, loss of access to common services, increased health risks, marginalisation and social disarticulation, all of which have compounded their vulnerability and chances of falling deeper into poverty. The paper also argues that compared to off-site and on-site resettlement displacees were less affected by negative consequences and impoverishment risks. The paper concludes with recommendations for slum resettlement policies of local government so that impoverishment risks can be reasonably averted.